The role of each groove on the behavior of twin axial groove journal bearings - Brito, F. P. (2007)
An experimental study of the role of each groove on the thermal behavior of a 50mm plain journal bearing with two axial grooves located at ±90º to the load line was carried out. The temperature profiles at the oil-bush interface, oil outlet temperature, oil flow rate through each groove and shaft locus, were measured for variable applied load and oil supply pressure. It was found that the cooling effect of the downstream groove is small for low eccentricities, becoming more relevant as eccentricity increases. The opposite phenomenon occurs at the upstream groove. The cooling effect is related to the flow rate in each groove. Under high load / low supply pressure negative flow rate at the upstream groove was detected. This phenomenon was found to affect dramatically the bearing performance. Increasing supply pressure yielded a decrease in shaft eccentricity along with a temperature decrease, especially for high loads.